Efektivitas Layanan Bimbingan Kelompok dengan Pendekatan Rational Emotive Behavior Therapy untuk Mengatasi Kecemasan Mahasiswa - Stevani, Hayu; Mudjiran, Mudjiran; Iswari, Mega (Universitas Negeri Padang, 2016)
Anxiety is unplesant feelings or tension against something that has not yet happened, and it could raise a fear of the impact that might grow. REBT regards an anxiety as an irrational thought that lead an individual to behave ineffectively, such as avoiding particular situation. Public speaking anxiety is a fear that is felt when speaking in front of many people. This fear could generate a variety of symptoms, such as sweating and even forget the words to be delivered. To avoid this condition, the individual choose to remain silent. Group guidance service is one of guidance an counseling serviced aimed at training members of the group to speak in front of public and be able to share ideas with others. The research was designed for revealing: the average score of the students’ anxiety before and after group guidance service assisted with REBT approach was applied by using ABCDE model and homework assigment technique, and the effectiveness of group guidance service assisted with REBT approach to reduce the student’ anxiety. This research applied quantitative method. This was a pre-experimental research which used the one group pretest and posttest design. The subject was chosen by using purposive sampling method. The subject of the research was seven students having high anxiety, medium anxiety and low anxiety. This research was conducted at IAIN Imam Bonjol Padang. The data gathered were analyzed by using statistic non-parametrik technique assisted with Wilcoxon Signed Rank Test and SPSS version 20.00. The result of the research showed that there was a difference between the average score of the students’ anxiety before and after the treatment given in which their pretest score was 136,1 and their posttest score was 111,5. Futhermore, the result of hypothesis test indicated that the score of Asymp. Sig (2-tailed) was 0,005 which was below alpha 0,05 (0,005<0,05). Hence, Ho was rejected and Ha was accepted. Based on these result, it was concluded that the use of group guidance service assisted with REBT approach which was applied by using ABCDE model and homework assigment technique was effective to overcome the students’ anxiety to speak in front of people (in the class).